Examen especial a los componentes bienes y servicios de consumo y bienes de larga duración en la Dirección Distrital 11D03-Paltas-Salud, período 2014 - Bravo Herrera, Mónica Gabriela (2016)
The present titling work called "SPECIAL EXAMINATION OF CONSUMER GOODS AND CONSUMER SERVICES AND LONG-TERM ASSETS IN DISTRICT ADDRESS 11D03-PALLETS-HEALTH, PERIOD 2014", was performed to fulfill a prerequisite to opt for the title of Engineering in Accounting and Auditing Public Accountant Auditor at the National University of Loja. The main purpose of the Special Review was to achieve the objectives; Evaluate the internal control system applied to the components of consumer goods and services and long-lived assets where I was able to determine compliance with legal and regulatory provisions, apply the three phases of financial audit that includes Planning, Execution and Communication of Results , Which was carried out through the use of various techniques and procedures and to prepare a special review report with its respective comments, conclusions and recommendations, which will enable the highest authorities to take appropriate corrective measures to strengthen those weaknesses encountered Which were: Procurement is not carried out in accordance with the CAP and therefore is not purchased in the appropriate quantities; When the reception and entry of the products to warehouse does not exist a technical analysis to verify if it is receiving according to the requested, the warehouses to store the acquired products do not have the sufficient space to be sheltered, With an internal regulation that allows to regulate the use, care and transfer of long-lived assets in the institution, there are assets that are damaged or in bad conditions due to lack of preventive and corrective maintenance, no permanent physical findings have been made, producing There are goods in bad condition without having discharged them.